Synthesis of magnetic core/shell carbon nanosphere supported manganese catalysts for oxidation of organics in water by peroxymonosulfate - Wang, Yuxian; Sun, Hongqi; Ang, Ming; Tade, Moses; Wang, Shaobin (Academic Press, 2014)
Magnetic separation is more cost-effective than conventional separation processes in heterogeneous catalysis, especially for ultrafine nanoparticles. Magnetic core/shell nanospheres (MCS, Fe3O4/carbon) were synthesized by a hydrothermal method and their supported manganese oxide nanoparticles (Mn/ MCS) were obtained by redox reactions between MCS and potassium permanganate at a low temperature. The materials were analyzed by a variety of characterization techniques such as powder X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), energy-dispersive X-ray spectrometer (EDS), Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA) and N2 adsorption/desorption. The Mn/MCS catalysts were able to effectively activate Oxone for phenol degradation in aqueous solutions. Nitrogen treated MCS supported Mn achieved 100% conversion within 120 min. Kinetic studies showed that phenol degradation over supported Mn catalysts follows the first order kinetics. It was also found that the catalysts can be easily separated from the aqueous solutions by an external magnetic field. The Oxone activation mechanism by Mn/MCS catalysts was discussed and sulfate radicals were suggested to be the primary reactive species generated from peroxymonosulfate (PMS) for phenol catalytic oxidation.